Community characteristics and distribution patterns of soil fauna after vegetation restoration in the northern Loess Plateau - Xi Yang (Elsevier, 2021)
The relationship between soil fauna and vegetation diversity has been of continuous concern. The effects of the “Grain-for-Green” program on the Loess Plateau in maintaining the abundance and diversity of soil fauna are poorly understood. This study assessed the spatial influence of five common artificial restoration habitats, Populus simonii, Pinus tabulaeformis, Caragana korshinskii, Medicago sativa, and Stipa bungeana, and one farmland habitat on the characteristics of soil fauna communities. Results showed that six soil fauna groups (Araneae, Acarina, Collembola, Isoptera, Coleoptera larvae, and Coleoptera adults) were shared among these habitats, accounting for 37.5% of the total number of groups. Acarina was the dominant group in each habitat. The soil fauna abundance in the P. tabulaeformis habitat was the highest among the habitats, reaching 7656 ind m−2. S. bungeana had the highest diversity, richness, and evenness indices of soil fauna among the habitats. Furthermore, a remarkable correlation among main soil properties (water content, organic carbon, and available potassium), litter properties (vegetation coverage, vegetation density, and litter thickness), and soil fauna were observed. The differences in microenvironment among the six habitats had a strong influence on the composition of soil fauna communities. Compared with other habitats, the S. bungeana habitat is more conducive to the protection of biodiversity. Vegetation restoration increases the diversity of soil fauna by improving their living environment, and soil fauna communities can be used as assessment indicators for “vegetation restoration benefits.” These findings help reveal the developmental tendencies of soil fauna during vegetation restoration in the Loess Plateau, and provide important support for evaluating environmental quality by soil fauna.